Seasonal comparison of gastrointestinal parasites in captive birds at FUNAAB Zoological Garden, Ogun state, Nigeria: Seasonal comparison of gastrointestinal parasites in captive birds (Bangladesh Journal of Animal Science, 2026)
Captive wild birds in zoological gardens play vital roles in the conservation and educational purposes but are highly vulnerable to gastrointestinal parasitism, which threatens their survival and welfare. This study investigated seasonal and interspecies variation in gastrointestinal parasites among six bird species housed at the Federal University of Agriculture, Abeokuta Zoological Garden, Nigeria. 46 fresh fecal samples were collected during rainy (August–September 2023) and dry (January–February 2024) seasons and analyzed using flotation technique, formol-ether concentration technique and McMaster egg count techniques. The results revealed marked seasonal differences in parasite prevalence and intensity, with higher burdens generally recorded during the rainy season. Common parasites included Ascaris spp, Entamoeba spp, Giardia spp, Strongyloides spp, and Ancyclostoma spp, with ostriches, geese, and mallard ducks showing the heaviest infections, particularly those with ground contact, as reflected by higher egg per gram (EPG) counts. Notably, Ascaris spp. infection intensity was highest in ostriches (40.75 ± 1.55 and 61.00 ± 1.41 EPG) and geese (33.75 ± 11.39 and 25.00 ± 2.87 EPG) during the rainy and dry seasons, respectively. Statistical analysis confirmed significant seasonal variation in key parasites, highlighting the influence of environmental conditions on transmission dynamics. These findings underscore the importance of seasonally informed parasite monitoring, targeted treatment schedules, and improved enclosure hygiene in zoological settings. Strengthening parasite control not only enhances avian welfare but also contributes to broader conservation outcomes in tropical zoos.Bangladesh Journal of Animal Science 54 (4): 91-100, 2025